2003
DOI: 10.5012/bkcs.2003.24.8.1126
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Learn from Two-Dimensional Raman Spectra by Varying the Polarization Conditions?

Abstract: The signals obtained from the 5 th -order (two-dimensional) Raman spectrum of a liquid can depend dramatically on the polarizations of the various light beams, but to date there has been no evidence presented that different polarization conditions probe any fundamentally different aspects of liquid dynamics. In order to explore the molecular significance of polarization we have carried out a molecular dynamics simulation of the 5 th -order spectrum of a dilute solution of CS2 in liquid Xe, perhaps the simplest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Much has been made of the presence of nodes in the molecular dynamics simulations of fifth-order Raman response of liquid CS 2 that are not present in the experimental response. , The presence of these nodes along the probe axis has been attributed to rotation−rotation coupling influencing the relative contributions to the signal of the intermolecular anharmonicity and the nonlinearity in the polarizability . An analysis performed by Ma and Stratt on a single CS 2 molecule in a liquid xenon bath indicates that these nodes are a common feature and that they are highly sensitive to the details of the potential and experimental protocols; for example, the positions of the nodes are strongly influenced by the polarization tensor element chosen. , On the basis of their polarization analysis in comparison with both the experimental results and the MD simulations, it appears possible that the MD simulation overestimates the contribution to the signal from the nonlinear dependence of the polarizability on coordinate. This is of concern because the response of liquid benzene also indicates the presence of nodes in both the experimental and simulated response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much has been made of the presence of nodes in the molecular dynamics simulations of fifth-order Raman response of liquid CS 2 that are not present in the experimental response. , The presence of these nodes along the probe axis has been attributed to rotation−rotation coupling influencing the relative contributions to the signal of the intermolecular anharmonicity and the nonlinearity in the polarizability . An analysis performed by Ma and Stratt on a single CS 2 molecule in a liquid xenon bath indicates that these nodes are a common feature and that they are highly sensitive to the details of the potential and experimental protocols; for example, the positions of the nodes are strongly influenced by the polarization tensor element chosen. , On the basis of their polarization analysis in comparison with both the experimental results and the MD simulations, it appears possible that the MD simulation overestimates the contribution to the signal from the nonlinear dependence of the polarizability on coordinate. This is of concern because the response of liquid benzene also indicates the presence of nodes in both the experimental and simulated response.…”
Section: Discussionmentioning
confidence: 99%
“…Without at least one of these two sources, no fifth-order Raman signal can exist. It was expected that in most liquids each of these sources will contribute to the signal, and early work in the field indicated it should be possible to separate the effects of the two contributions. , Over the years, intense theoretical efforts have used a variety of approaches to simulate the fifth-order Raman response of various systems, including multimode Brownian oscillator models, ,, harmonic oscillator models, normal-mode theory, molecular dynamics simulations, hydrodynamic theory, the generalized Langevin equation, classical time correlation functions, and finite-field molecular dynamics simulations. In several cases, this has required the development of new theories and computational approaches, with previous theories having proved inadequate at properly describing the liquid state. Collectively, the theoretical work in this area has demonstrated that the fifth-order Raman response is very sensitive to the details of the intermolecular potential and treatment of the liquid dynamics.…”
Section: Introductionmentioning
confidence: 99%